Streptococcal Receptor Polysaccharides: Recognition Molecules for Oral Biofilm Formation - Kolenbrander Paul E; Yang Jinghua; Palmer Robert J; Yoshida Yasuo; Cisar John O (BMC, 2006)
Abstract Background Strains of viridans group streptococci that initiate colonization of the human tooth surface typically coaggregate with each other and with Actinomyces naeslundii, another member of the developing biofilm community. These interactions generally involve adhesin-mediated recognition of streptococcal receptor polysaccharides (RPS). The objective of our studies is to understand the role of these polysaccharides in oral biofilm development. Methods Different structural types of RPS have been characterized by their reactions with specific antibodies and lectin-like adhesins. Streptococcal gene clusters for RPS biosynthesis were identified, sequenced, characterized and compared. RPS-producing bacteria were detected in biofilm samples using specific antibodies and gene probes. Results Six different types of RPS have been identified from representative viridans group streptococci that coaggregate with A. naeslundii. Each type is composed of a different hexa- or heptasaccharide repeating unit, the structures of which contain host-like motifs, either GalNAcβ1-3Gal or Galβ1-3GalNAc. These motifs account for RPS-mediated recognition, whereas other features of these polysaccharides are more closely associated with RPS antigenicity. The RPS-dependent interaction of S. oralis with A. naeslundii promotes growth of these bacteria and biofilm formation in flowing saliva. Type specific differences in RPS production have been noted among the resident streptococcal floras of different individuals, raising the possibility of RPS-based differences in the composition of oral biofilm communities. Conclusion The structural, functional and molecular properties of streptococcal RPS support a recognition role of these cell surface molecules in oral biofilm formation.